Critical theory diverse objects, diverse subjects - Lehmann, Jennifer M., 1956- (JAI, 2003)
The contributions in this 22nd volume of "Current Perspectives in Social Theory" explore the arguments for and against a view of the world in which multiple, distinct and conflicting societies differ both over time and contemporaneously.
Keywords: Social sciences -- Philosophy.; Knowledge, Theory of.; Social theory.; Social Science -- Sociology -- General.; elektronické knihy; electronic books